Implementasi Multi Criteria Decision Making Menggunakan Metode Simple Additive Weighting (SAW) Pada Sistem Pendukung Keputusan Promosi Kenaikan Jabatan - Eddy Kurniawan; Achmad Miftakhul Ilmi; Nufan Balafif (Jurnal Teknika, 2020)
Telkomsel Distribution Center (TDC) Jombang has problems in promoting employees to fill the Supervisor (SPV) and Branch Manager (BM) positions. TDC Jombang has several assessment criteria for employees to be able to fill SPV and BM positions. But in the assessment process, each criterion still tends to be subjective. In making decisions based on several criteria, a Multi-Criteria Decision Making (MCDM) approach can be used by applying the method that is considered most appropriate to produce the best alternative decision recommendations. This study aims to provide the best solution by implementing the Multi-Criteria Decision Making approach using the SAW (Simple Additive Weighting) method which will be programmed in a computer-based decision support system (SPK). The SAW method was chosen because it can weigh the values on each attribute and rank to get the best alternative recommendations. The data used are Jombang TDC employee data. From this study, it was obtained that the use of the SAW method programmed in the SPK succeeded in presenting information comparing the value of preferences between candidates. Candidates with the highest preference value are the most recommended alternatives to choose